A New Approach to the design of DC Powered Induction Cooker - Adhikari, Bikal; Shrestha, Jagan Nath; Shakya, Shree Raj (Kathford Journal of Engineering and Management, 2018)
About 80 % of total energy consumption in Nepal is being consumed in the residential sector and about 60 % of total residential energy application includes cooking application. At present, in urban area, there is heavy dependence on liquefied petroleum gas for cooking purpose whereas in rural area, there is heavy dependence on biomass. Clearly, there is a need to switch towards clean and efficient fuel: electricity. Load shedding problem has been a reason preventing Nepalese people to switch towards electricity based cooking. Even though at present (2017), Nepal Electricity Authority’s has been able to reduce load shedding for residential consumers, there is still a condition of inadequate supply of electricity if all of the consumers will switch towards electricity for cooking purpose. The experimental and simulation efficiency of conventional AC based induction cooker has been found to be 85.56 % and 87 % respectively. DC powered induction cooker has been designed and simulated. The simulation efficiency of which has been measured to be 90.10 %. The hardware realization of the design is malfunctioning in real time testing making a need of power electronic component with the capacity to pass very high current, as high as 80 A at low voltage, as low as 12 V.